Use of Environmental DNA to Determine Fantail Darter (Etheostoma flabellare) Density in a Laboratory Setting: Effects of Biomass and Filtration Method - Guivas, Ramon A.; Brammell, Ben F. (International Journal of Zoology, 2020)
Estimating fish abundance/biomass holds great importance for freshwater ecology and fisheries management, but current techniques can be expensive, time-consuming, and potentially harmful to target organisms. Environmental DNA (eDNA) has proven an effective and efficient technique for presence/absence detection of freshwater vertebrates. Additionally, recent studies report correlations between target organism density/biomass and eDNA levels, although widespread application of this technique is limited by the number of studies examining this relationship in various species and settings. Additionally, filter clogging is a commonly encountered issue in eDNA studies in environments with significant sediment and/or phytoplankton algae. Frequently, a sample must be split into multiple aliquots and filtered separately in order to process the entire sample. The present study examines both the relationship between biomass and eDNA and the effects of single versus multiple filter sampling on eDNA concentrations of fantail darters (Etheostoma flabellare) in a laboratory setting. Tank tests were performed in quadruplicate at four environmentally relevant fantail biomass levels. eDNA samples were collected and processed in parallel (one as a whole through a single filter and one in parts through multiple filters). Species-specific primers and a probe were developed for E. flabellare from cytochrome b sequences obtained from locally collected specimens, and real-time quantitative PCR was used to analyze eDNA levels at each biomass. Significant correlations were observed with increasing biomass for both methods, although this relationship was stronger for samples processed by the multiple filter method. These data should be useful in eDNA studies in which turbidity necessitates the use of multiple filters per sample as well as in the use of eDNA to estimate darter populations.